THE RELATIONSHIP BETWEEN BLOOD PRESSURE AND BLOOD SUGAR LEVELS: THE MODERATING ROLE OF AGE AND GENDER - Wahyudin, Wahyudin; Pauzi, Rizqi Yanuar; Yunika, Novia; Setyanto, Muhamad Rifqi; Hidayah, Arfi Nurul (Medical and Health Journal, 2025)
This study aimed to evaluate the relationship between blood pressure and blood sugar levels, and how age and gender moderate the relationship. The study involved 105 respondents who underwent health check-ups in Banyumas Regency. Blood pressure was categorized as normal or hypertension, while blood sugar levels were divided into normal, prediabetes, and diabetes. The Chi-Square test showed a significant association between blood pressure and blood sugar levels (p < 0.05), although the strength of the association was relatively weak. Individuals with hypertension have a higher risk of developing blood sugar disorders, especially in women and individuals over 45 years old. Ordinal regression analysis showed that age and gender played an important role in influencing this association. These findings emphasize the importance of an integrated approach in screening and management of hypertension and diabetes, to prevent long-term complications such as cardiovascular disease and renal failure. The practical implications of this study can be used to design more effective public health programs